1997
DOI: 10.1046/j.1365-313x.1997.12051011.x
|View full text |Cite
|
Sign up to set email alerts
|

An Arabidopsis mutant showing reduced feedback inhibition of photosynthesis

Abstract: SummaryMany plant genes are responsive to sugars but the mechanisms used by plants to sense sugars are unknown, A genetic approach has been used in Arabidopsis to identify genes involved in perception and transduction of sugar signals. For this purpose, an in vivo reporter system was established consisting of the light-and sugar-regulated plastocyanin promoter, fused to the luciferase coding sequence (PC-LUC construct). At the seedling stage, expression of the PC-LUC gene is repressed by sucrose, and a number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 31 publications
3
43
0
Order By: Relevance
“…The availability of the sugar-signaling sun6 mutant, which was previously isolated in our laboratory (Dijkwel et al, 1997), allowed us to further test whether Man blocks germination via a HXK-mediated process. sun6 was isolated for its insensitivity to Suc, a disaccharide that can readily be converted to Glc and Fru, both of which are HXK substrates.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The availability of the sugar-signaling sun6 mutant, which was previously isolated in our laboratory (Dijkwel et al, 1997), allowed us to further test whether Man blocks germination via a HXK-mediated process. sun6 was isolated for its insensitivity to Suc, a disaccharide that can readily be converted to Glc and Fru, both of which are HXK substrates.…”
Section: Discussionmentioning
confidence: 99%
“…Photosynthesis and expression of photosynthesis genes show a reduced sensitivity to repression by the Glc analog 2-deoxyglucose in sun6 compared with the wild type. Seedling development in this mutant has also been found to be insensitive to high concentrations of Glc (Van Oosten et al, 1997), and Van Oosten et al (1997) proposed that the sun6 mutation affects a process involved in the HXK-mediated signal transduction pathway. When tested for its capacity to germinate on Man, we found that sun6 displays a significantly greater insensitivity to this Glc analog than the wild type.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This transient increase in PC mRNA and luciferase activity levels can be repressed by SUC. Mutants defective in SUC repression were identified on the basis of high luminescence levels when grown on plates with 3% SUC (Dijkwel et al, 1997). Such Suc-mcoupled (sun) mutants show no or reduced SUC repression of luminescence.…”
Section: Sugar-sensing Mutantsmentioning
confidence: 99%